Psychological Consequences of the Most Common Dermatoses: Data from the Objectifs Peau Study - Laurent Misery; Charles Taïeb; Martine Schollhammer; Sylviane Bertolus; Eva Coulibaly; Nathalie Feton-Danou; Laurence Michel; Jean-Christophe Seznec; Julie Versapuech; Pascal Joly; Florence Corgibet; Khaled Ezzedine; et al. (Medical Journals Sweden, 2020)
The prevalence of psychological disorders in patients with common skin diseases was assessed in a large representative sample of the French adult population. General health, as measured by the EQ5D score, was significantly lower if patients reported having rosacea, atopic dermatitis, urticaria, fungal infections, psoriasis or acne. The proportions of participants reporting being extremely anxious or depressed were higher in those who reported having rosacea, atopic dermatitis or contact dermatitis. Difficulties in sexual and conjugal life were frequently reported by people with psoriasis, atopic dermatitis, contact dermatitis, urticaria and, in particular, acne. Sleep disorders were present in 30-50% of those who reported having acne, rosacea, eczema, psoriasis or urticaria. Sleep disorders may be related not only to pruritus, but also to disfiguring skin diseases. Anxiety and depression complications were mainly reported by those with disfiguring diseases. Sexual and conjugal dysfunctions were associated with all dermatoses (with the exception of warts).